The potential of targeting autophagy-related non-coding RNAs in the treatment of lung cancer - Li, Juan; Gan, Jimei; Shi, Shenggan; Huang, Juying; Yang, Yong (Frontiers in Pharmacology, 2025)
Lung cancer is the most prevalent malignant tumor worldwide and remains the leading cause of cancer-related mortality. Despite advances in treatment development, lung cancer patients often face poor quality of life and low survival rates. Increasing evidence highlights the significant roles of autophagy and non-coding RNAs (ncRNAs) in the initiation, progression, and therapeutic response of lung cancer. Autophagy and ncRNAs can function as both tumor-promoting and tumor-suppressing factors in lung cancer. Therefore, investigating the roles of autophagy and ncRNAs in lung cancer provides valuable insights into its pathophysiology. At the same time, non-coding RNA also plays an important role in regulating autophagy. This study reveals that autophagy affects the occurrence and development of lung cancer through multiple pathways. Then, we also studied that in lung cancer, ncRNAs (e.g., lncRNAs, miRNAs, circRNAs and piRNAs) can regulate autophagy to promote or inhibit tumorigenesis, metastasis and drug resistance in lung cancer. Finally, the problems and solutions of autophagy and ncRNAs in the treatment of lung cancer were explored. These findings suggest that autophagy and ncRNAs can be potential targets for the treatment of lung cancer.